Illuminating the future of food microbial control: From optical tools to Optogenetic tools - Wang, Yuwei; Li, Mengyu; Liu, Wei; Jiang, Ling (Food chemistry, 2025)
Light as an environmental signal can effectively regulate various biological processes in microbial systems. Optical and optogenetic tools are able to utilize light for precise control methods with minimal interference. Recently, research on these tools has extended to the field of microbiology. Distinguishing from existing reviews, this review narrows the scope of application into food sector, focusing on advances in optical and optogenetic tools for microbial control, including optical tools targeting pathogenic or probiotic bacteria for non-thermal sterilization, antimicrobial photodynamic therapy, or photobiomodulation, combined with nanomaterials as photosensors for food analysis. As well as using optogenetic tools for more convenient and precise control in food production processes, covering reversible induction, metabolic flux regulation, biofilm formation, and inhibition. These tools offer new solutions to goals that cannot be achieved by traditional methods, and they are still maturing to explore other uses in the food field. Application of emerging technologies (optical tools and optogenetic tools) in food microorganism. Optics tools (ultraviolet, LED and pulsed light) are dedicated to regulate food microorganism, killing pathogenic bacteria (Salmonella, Escherichia coli O157:H7 and Vibrio etc.) or regulating probiotics, such as Bacillus amyloidus, Lactobacillus and Acetobacter pasteurianus in blueberries, kimchi, milk and vinegar. Nanomaterials (Up-converting phosphors, UCPs, quantum dots, QDs, Carbon nanodots, CDs, nanoparticles, NPs) were used as optical sensors for quantitative and rapid detection to determine food safety. Optogenetic tools (EL222, Cry2-CIB1, YF1/FixJ, PhyB-PIF, CcaS/R and UirS/R) can be used as inducers or dynamically switches to participate in the production of food-related chemicals and the regulation of metabolic flow, and can also have an effect on the formation and inhibition of biofilms. [Display omitted] •Optical tools can eliminate pathogens & regulate probiotics to boost food quality.•Optical tools with advanced oxidation process (AOP) to improve sterilizing effect.•Optical tools with nanomaterials for pathogens detection.•Optogenetic tools can dynamically control food microorganisms process conveniently.•Optogenetic tools integrating biofilms for dynamic control have promising routes.